“Nivel de absorción de la raíz de Cortaderia rudiuscula Stapf. “cortadera” al plomo y hierro, en condiciones de laboratorio” - Altamirano Slee, Cinthia Esthefany (2017)
Phytoremediation can be defined as a sustainable technology that is based on the use of plants to reduce in situ the concentration or danger of organic and inorganic contaminants in soil, sediments, water and air. The objective of the present research work was to determine the level of absorption of the roots of Cortaderia rudiuscula Stapf. "cortadera" exposed to lead and iron at concentrations of 0.00 10.0, 20.0 and 30.0 ppm under laboratory conditions. The biological material was collected in areas adjacent to the Chanchacap River (Chanchacap, Agallpampa, Otuzco, La Libertad); the experimental work was carried out in the Environmental Genotoxicity Laboratory of the Academic Department of Biological Sciences of the National University of Trujillo. The experimental unit was the plant C. rudiuscula, exposed to lead and iron; under photo-lighting for 13 days, lead and iron solutions were prepared. An experimental design with four treatments and three repetitions was used. By means of the flame atomic absorption spectrophotometry method, the levels of lead and iron absorbed by the roots of the plant were determined. The main levels of lead and iron absorption were found in the treatments of 20 and 30 ppm, thus demonstrating the cumulative capacity of the roots of C. rudiuscula. The data were some of the tests of Anova and Tukey.